PREFERENSI DAN EFIKASI RODENTISIDA BRODIFAKUM TERHADAP TIGA JENIS TIKUS HAMA - Swastiko Priyambodo; Rizky Nazarreta (Agrovigor, 2013)
Rat which is associated with wildlife and human life becomes important pest in agriculture, plantations, and settlements.  Currently, three species of rat pest that presence in human live is very annoying and causing damage, i.e. ricefield rat (Rattus argentiventer), house rat (R. rattus diardii), and tree rat (R. tiomanicus).  Efforts to control the three rat species are often done using chemical control (rodenticides).  The aims of this study are comparing the consumption of ricefield rats, house rats, and tree rats to rodenticide with brodifacoum active ingredient.  Besides, the aim is to understand the effectiveness of these rodenticides to control the three rats’ species.  The method used is multiple-choice test and bi-choice test for five days continuously using brodifakum and bait base (grain, rice, corn).  After five days treatment, test rats will be re-tested for three days with grain fed, then will be used for further treatment, if in good health.  Results obtained from the multiple choice test showed relatively similar results, namely that the rats chose to consume more feed than rodenticides.  The method of bi-choice test, rats preferred rice when giving feed, rather than corn and paddy. Rodenticides brodifacoum for ricefield rats is less favored on any provision of feed.  Brodifacoum is more effective in controlling house and tree rats, because the two species are less recognized and did not experience to the suspicion of rodenticide. Key words: rodenticides brodifacoum, ricefield rat, house rat, and tree rat